"Every time someone comes forward, it makes it easier for the next survivor to be heard": Sport as a triggering agent to break the silence of child sexual abuse. Issue 3 (27th May 2019) - Sanderson, Jimmy; Weathers, Melinda R.
Abstract : This research explored cultures of silence around child sexual abuse (CSA). On July 10, 2018, in response to multiple sexual abuse cases occurring in sport, sport news site Deadspin published a reader letter detailing CSA. This article prompted others to comment by sharing their accounts of CSA. Through qualitative analysis of 47 posts, we analyzed CSA victims' lived experiences, with a focus on how cultural and social forces silenced them. Results indicated that silencing of CSA victims occurred through three overarching mechanisms: (a) patriarchal master narrative; (b) trauma-related shame; and (c) systemic power. The results illuminate the cultural and social factors that CSA victims experience and provide opportunities for parents, family members, and other stakeholders to better understand these constraints. In doing so, victims can be better supported, and needed discourse on CSA can occur more frequently to help identify solutions to this pervasive social problem.